2017
DOI: 10.1002/bit.26248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of highly selective MMP‐14 inhibitory Fabs by deep sequencing

Abstract: Matrix metalloproteinase (MMP)-14 is an important target for cancer treatment due to its critical roles in tumor invasion and metastasis. Previous failures of all compound-based broad-spectrum MMP inhibitors in clinical trials suggest that selectivity is the key for a successful therapy. With inherent high specificity, monoclonal antibodies (mAbs) therefore arise as attractive inhibitors able to target the particular MMP of interest. As a routine screening method, enzyme-linked immunosorbent assays (ELISA) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…However, the high similarity of protein folding and catalytic chemistry among MMP family members presents a daunting challenge for the generation of highly selective compound inhibitors (Turk, ). Our studies (Lopez, Nam, Kaihara, Mustafa & Ge, ; Nam, Fang, Rodriguez, Lopez, & Ge, ; Nam, Rodriguez, Remacle, Strongin, & Ge, ), among others (Appleby et al, ; Devy et al, ; Ling et al, ; Udi et al, ), demonstrated the feasibility that antibody‐based inhibitors could exhibit the desired high selectivity. Particularly, Fab3A2 with 4.8 nM affinity, 9.7 nM potency, and high selectivity toward MMP‐14 was isolated from a library containing ultralong CDR H3s (Nam et al, ).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the high similarity of protein folding and catalytic chemistry among MMP family members presents a daunting challenge for the generation of highly selective compound inhibitors (Turk, ). Our studies (Lopez, Nam, Kaihara, Mustafa & Ge, ; Nam, Fang, Rodriguez, Lopez, & Ge, ; Nam, Rodriguez, Remacle, Strongin, & Ge, ), among others (Appleby et al, ; Devy et al, ; Ling et al, ; Udi et al, ), demonstrated the feasibility that antibody‐based inhibitors could exhibit the desired high selectivity. Particularly, Fab3A2 with 4.8 nM affinity, 9.7 nM potency, and high selectivity toward MMP‐14 was isolated from a library containing ultralong CDR H3s (Nam et al, ).…”
Section: Introductionmentioning
confidence: 61%
“…Our studies (Lopez, Nam, Kaihara, Mustafa & Ge, 2017;Nam, Fang, Rodriguez, Lopez, & Ge, 2017;Nam, Rodriguez, Remacle, Strongin, & Ge, 2016), among others (Appleby et al, 2017;Devy et al, 2009;Ling et al, 2017;Udi et al, 2015), demonstrated the feasibility that antibody-based inhibitors could exhibit the desired high selectivity.…”
mentioning
confidence: 61%
“…Furthermore, the expression level at 30 °C was two-fold higher than that at 37 °C. In addition, there was a band with an apparent MW of ~35 kDa in the 37 °C culture sample (arrow in Fig 5B), likely due to a low degree of cleavage at the long CDR-H3 region, observed phenomena for certain protease inhibitory antibodies [24, 25]. But the level of truncated Fab was reduced when cultured at 30 °C.…”
Section: Resultsmentioning
confidence: 88%
“…active‐site zinc‐chelating hydroxamates, have been tested in clinical trials but all failed due to low overall efficacy and severe side effects such as musculoskeletal pain and inflammation caused by poor selectivity . Compared to small molecule inhibitors, monoclonal antibodies (mAbs) usually render exclusive specificity, and have emerged as a promising alternative for MMP inhibition . In our previous study, a panel of Fabs inhibiting MMP‐14 was isolated from a phage displayed synthetic human antibody library carrying long CDR‐H3s .…”
Section: Introductionmentioning
confidence: 99%
“…17 Compared to small molecule inhibitors, monoclonal antibodies (mAbs) usually render exclusive specificity, and have emerged as a promising alternative for MMP inhibition. [19][20][21][22][23][24][25][26] In our previous study, a panel of Fabs inhibiting MMP-14 was isolated from a phage displayed synthetic human antibody library carrying long CDR-H3s. 27 Particularly, Fab 3A2 exhibited nM potency competitive inhibition toward MMP-14 with no reactivity with MMP-2 or -9.…”
Section: Introductionmentioning
confidence: 99%